Determination of upper flammability limits of C[sbnd]H[sbnd]O compounds in air at reference temperature and atmospheric pressure - Mendiburu, Andrés Z. [UNESP]; de Carvalho, João A. [UNESP]; Coronado, Christian R. (Elsevier, 2017)
The objective of the present article was to develop and validate a method for the determination of the upper flammability limits (UFLs) in air, at atmospheric pressure and reference temperature, of flammable compounds containing carbon, hydrogen and oxygen in their molecules, called C[sbnd]H[sbnd]O compounds for simplicity. The developed method applies basic combustion theory and chemical equilibrium. The upper flammability limits are determined by correlating a parameter named θ, which is the ratio of the adiabatic flame temperature at the stoichiometric composition to the adiabatic flame temperature at the UFL composition. A total set of 208 C[sbnd]H[sbnd]O compounds was considered, it was divided into a correlation set of 136 compounds and a prediction set of 72 compounds. The method's accuracy was tested in terms of the average of the absolute values of the relative errors (AARE) and in terms of the squared correlation coefficient (R2). Also, the 95% confidence interval was determined. For the correlation, prediction and total sets the AAREs were 9.66%, 7.63% and 8.95%, respectively. The R2 was 0.9382 for the correlation set, 0.9188 for the prediction set, and 0.9346 for the total set.
Keywords: Confidence interval; C[sbnd]H[sbnd]O compounds; Estimation; Upper flammability limits